Serotonin transporter density in isolated rapid eye movement sleep behavioral disorder - Garwood, Mark; Vijayakumar, Punithavathy; Bohnen, Nicolaas I.; Koeppe, Robert A.; Kotagal, Vikas (Frontiers in Sleep, 2024)
Background/objective The serotoninergic nervous system is known to play a role in the maintenance of rapid eye movement (REM) sleep. Serotoninergic projections are known to be vulnerable in synucleinopathies. To date, positron emission tomography (PET) studies using serotonin-specific tracers have not been reported in isolated REM sleep behavior disorder (iRBD). Methods We conducted a cross-sectional imaging study using serotonin transporter (SERT) 11C-3-amino-4-(2-dimethylaminomethyl-phenylsulfaryl)-benzonitrile (DASB) PET to identify differences in serotonin system integrity between 11 participants with iRBD and 16 older healthy controls. Results Participants with iRBD showed lower DASB distribution volume ratios (DVRs) in the total neocortical mantle [1.13 (SD: 0.07) vs. 1.19 (SD: 0.06); t = 2.33, p = 0.028)], putamen [2.07 (SD: 0.19) vs. 2.25 (SD: 0.18); t = 2.55, p = 0.017], and insula [1.26 (SD: 0.11) vs. 1.39 (SD: 0.09); t = 3.58, p = 0.001]. Paradoxical increases relative to controls were seen in cerebellar hemispheres [0.98 (SD: 0.04) vs. 0.95 (SD: 0.02); t = 2.93, p = 0.007)]. No intergroup differences were seen in caudate, substantia nigra, or other brainstem regions with the exception of the dorsal mesencephalic raphe [3.08 (SD: 0.53) vs. 3.47 (SD: 0.48); t = 2.00, p = 0.056] that showed a non-significant trend toward lower values in iRBD. Conclusions Insular, neocortical, and striatal serotoninergic terminal loss may be common in prodromal synucleinopathies before the onset of parkinsonism or dementia. Given our small sample size, these results should be interpreted as hypothesis-generating/exploratory in nature.